Educator Dignity: Recontextualizing the Javanese Ethical Wisdom of Ajining Diri Saka Lathi for Humanizing Pedagogical Communication in Elementary Education - Bambang Edi Siswanto; Wahyu Sukartiningsih; Maryam Isnaini Damayanti; Nurul Istiq'faroh; Zulfin Rachma Mufidah (Journal of Current Studies in SDGs, 2027)
Objective: To analyze the crisis of pedagogical communication and the need to strengthen educator dignity through the recontextualization of Javanese ethical wisdom, Ajining Diri Saka Lathi, into a Humanizing Pedagogical Communication Framework for elementary education. The study contributes to Sustainable Development Goal (SDG) 4 by promoting inclusive, ethical, and human-centered quality education. Method: To employ an Educational Design Inquiry (EDI) approach comprising three iterative phases: Analysis and Exploration, Design-Oriented Inquiry, and Enactment and Reflective Inquiry. Data were collected through a Systematic Literature Review (SLR), classroom observations, and Focus Group Discussions (FGDs). The enactment involved two pre-service elementary school teachers from Universitas Negeri Surabaya and two Grade V classroom teachers. Data were analyzed using thematic synthesis and reflective analysis to identify design requirements, evaluate the framework, and refine the design artifact. Results: The study developed the Humanizing Pedagogical Communication Framework by transforming five ethical values of Ajining Diri Saka Lathi, namely unggah-ungguh, tepa selira, andhap asor, angon rasa, and kamanungsan, into four pedagogical communication constructs: Ethical Identity, Relational Respect, Reflective Moral Self-Regulation, and Humanizing Pedagogical Dialogue. The enactment demonstrated the emergence of dignity-centered practices through Respectful Interaction, Dialogic Engagement, and Learner Empowerment, supporting SDG 4 and strengthening ethical relationships in educational institutions. Novelty: The study introduces a novel recontextualization of Ajining Diri Saka Lathi as the conceptual foundation of educator dignity, operationalized through the Humanizing Pedagogical Communication Framework as Educational Design Knowledge for promoting contextualized and humanizing pedagogical communication in elementary education.